Developing Thematic Box Media with Illustrations for Social Sciences: Enhancing Student Engagement in Learning the History of Islam’s Arrival Based on Surah Al-Hasyr Verse 18 - Sajidah, Adelia; Yusnaldi, Eka (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to develop illustrated thematic box media for Social Studies, specifically focusing on the material about the History of the Entry of Islam from the perspective of Surah Al-Hasyr, Verse 18, at SMPN 1 Pagar Merbau. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The validation results from material, media, and language experts indicate that the media is suitable for use, with an average score exceeding 75%. The practicality test conducted by teachers yielded a result of 88%, indicating that the media is practical for use in the learning process. Meanwhile, the results of a limited trial with 35 students showed a feasibility level of 98.85%, accompanied by an increase in learning outcomes, with a standard gain value of 0.355, which falls into the moderate category. The results of the Independent Samples t-Test revealed a significant difference between the experimental and control classes (Sig. 0.000 < 0.05), with the average learning outcomes of students in the experimental class being 9.42 points higher. Therefore, the illustrated thematic box media has proven to be effective in enhancing students’ understanding, motivation, and involvement in interactive and contextual Social Studies learning, and is capable of integrating Islamic values through a thematic approach.